Visual and somatosensory evoked potentials abnormalities among Behçet’s disease patients and their relation to disease activity, severity and antiphospholipid antibodies: a cross-sectional study - Ghada S. Nageeb; Enass A. Eliwa; Ibrahim Tharwat; Lamiaa A. Mohammad; Nada Alaa Attia (Egyptian Rheumatology and Rehabilitation)
Abstract Background Behçet’s disease (BD) is a common disease with high morbidity and mortality. Ocular, neurological, and vascular affection in BD are a major cause of such morbidity and mortality. Evoked potential (EP) studies including visual evoked potentials (VEP) and somatosensory evoked potentials (SSEP) in addition to antiphospholipid antibodies (aPL) are valuable tools for detection of ocular, neurological and vascular affection and may be used for assessment of activity and severity in BD. We aimed to use EP studies and aPL as objective tools in BD assessment. Results Abnormal VEP was found in 76% of BD patients and has a significant association with ocular involvement (P = 0.003), Moreover, Abnormal VEP was significantly associated with ocular activity (P = 0.002). Abnormal SSEP in both median and tibial nerves was found in 62% of patients, prolonged central conduction time of median and tibial nerves was found in 46% and 22% of patients respectively and was significantly associated with neurological involvement in BD (P < 0.05). Abnormal VEP and SSEP studies were significantly associated with BD disease severity (P < 0.05) but not activity. Vascular involvement was significantly associated with elevated lupus anticoagulant and anti-cardiolipin IgM antibodies (P < 0.05), elevated lupus anticoagulant levels were associated with optic nerve involvement and abnormal VEP. Conclusion Abnormal VEP and SSEP studies can be considered as indicators for BD severity and hence poorer prognosis. VEP study is a valuable tool in BD and may indicate ocular involvement or ocular activity. Prolonged Central conduction time of upper limb and lower limb evaluated by N13- N20 IPL and N22-P39 IPL respectively may be used to detect nervous system involvement in BD patients. Optic nerve involvement may be suspected in BD patients with elevated lupus anticoagulant, elevated LA and aCL IgM can be used as indicators for vascular involvement in BD.